Pengaruh Media Booklet Berwarna Tentang Menstruasi Terhadap Peningkatan Pengetahuan Siswi SD Di Kecamatan Cigudeg - Caroline Widjaja; Titin Yusnita; Hana Lestari (Institut Agama Islam Sahid (INAIS) Bogor, 2022)
This study aims to determine the effect of the color booklet media about menstruation on increasing the knowledge of elementary school students in Tipar Elementary School, Cigudeg District, Bogor Regency. This research is a quasy experimental study with a pre- posttest with control design method that was conducted on grade V and IV students who had or had not yet menstruated and were selected using random sampling techniques with 40 respondents who were divided into 20 respondents in the control group using black booklet media white and 20 respondents in the experimental group using a color booklet. The results showed the average score of students who used colored booklet media was higher than students who used black and white booklets, but had the same increase in knowledge and after being compared using the independent sample t test, the results showed no significant effect between increased knowledge colored booklet and black and white booklet.